Picosecond Laser Etching of Glass Spiral Microfluidic Channel for Microparticles Dispersion and Sorting - Rong Chen; Shanshan He; Xiansong He; Jin Xie; Xicong Zhu (Micromachines)
In microfluidic chips, glass free-form microchannels have obvious advantages in thermochemical stability and biocompatibility compared to polymer-based channels, but they face challenges in processing morphology and quality. Hence, picosecond laser etching with galvanometer scanning is proposed to machine spiral microfluidic channels on a glass substrate. The objective is to disperse and sort microparticles from a glass microchip that is difficult to cut. First, the micropillar array and the spiral microchannel were designed to disperse and sort the particles in microchips, respectively; then, a scanning path with a scanning interval of 5 μm was designed according to the spot diameter in picosecond laser etching; next, the effects of laser power, scanning speed and accumulation times were experimentally investigated regarding the morphology of spiral microchannels; finally, the microfluidic flowing test with 5 μm and 10 μm microparticles was performed to analyze the dispersing and sorting performance. It was shown that reducing the laser power and accumulation times alongside increasing the scanning speed effectively reduced the channel depth and surface roughness. The channel surface roughness reached about 500 nm or less when the laser power was 9 W, the scanning speed was 1000 mm/s, and the cumulative number was 4. The etched micropillar array, with a width of 89 μm and an interval of 97 μm, was able to disperse the different microparticles into the spiral microchannel. Moreover, the spiral-structured channel, with an aspect ratio of 0.51, significantly influenced the velocity gradient distribution, particle focusing, and stratification. At flow rates of 300–600 μL/min, the microparticles produced stable focusing bands. Through the etched microchip, mixed 5 μm and 10 μm microparticles were sorted by stable laminar flow at flow rates of 400–500 μL/min. These findings contribute to the design and processing of high-performance glass microfluidic chips for dispersion and sorting.